2015
DOI: 10.1186/s12864-015-1967-5
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated analysis of the local and systemic changes preceding the development of post-partum cytological endometritis

Abstract: BackgroundThe regulation of endometrial inflammation has important consequences for the resumption of bovine fertility postpartum. All cows experience bacterial influx into the uterus after calving; however a significant proportion fail to clear infection leading to the development of cytological endometritis (CE) and compromised fertility. We hypothesised that early immunological changes could not only act as potential prognostic biomarkers for the subsequent development of disease but also shed light on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 77 publications
2
43
0
1
Order By: Relevance
“…Previous studies on RNA-seq analysis in mixed bovine epithelial and stromal endometrial cells treated with LPS showed 20 differentially-expressed miRNAs and 108 DEGS, as well as enriched 118 GO and 66 KEGG pathways connected to them [14]. In addition, a previous study on RNA-seq analysis of change in miRNA and mRNA expression in 15 cows at 7 and 21 days postpartum showed 4197 DEGs in healthy cows, while only 31 genes were differentially expressed in cows with cytological endometritis from proinflammatory to hyperplasia stages [15]. Other studies have been performed on RNA-seq analysis of effects of LPS on whole transcriptome of bovine endometrial epithelial cells with focus on genes involved in embryo-maternal interactions.…”
mentioning
confidence: 84%
“…Previous studies on RNA-seq analysis in mixed bovine epithelial and stromal endometrial cells treated with LPS showed 20 differentially-expressed miRNAs and 108 DEGS, as well as enriched 118 GO and 66 KEGG pathways connected to them [14]. In addition, a previous study on RNA-seq analysis of change in miRNA and mRNA expression in 15 cows at 7 and 21 days postpartum showed 4197 DEGs in healthy cows, while only 31 genes were differentially expressed in cows with cytological endometritis from proinflammatory to hyperplasia stages [15]. Other studies have been performed on RNA-seq analysis of effects of LPS on whole transcriptome of bovine endometrial epithelial cells with focus on genes involved in embryo-maternal interactions.…”
mentioning
confidence: 84%
“…A successful immune response in a healthy cow is able to resolve the inflammatory state postpartum to a regular or homeostatic state within a period of one to three weeks. Cows that develop endometritis or SCE are not able to do this and maintain the inflammatory response for a longer period (Foley et al, 2015).…”
Section: Development Of Uterine Diseasementioning
confidence: 99%
“…IL-8 and acute phase proteins e.g. α1-Acid Glycoprotein (AGP), produced by endometrial epithelial cells and local immune populations are increased in inflamed uterine tissue and in vitro models [ 6 8 ]. These inflammatory biomarkers have been detected in uterine mucus and CVM [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%